235 Airborne and internal exposure to chromium among welders. (11th October 2013) - Lotz, A L; Weiss,; Pesch,; Van, Gelder; Hahn,; Brüning,
Abstract : Objectives: The objective of this analysis was to investigate levels and determinants of exposure to respirable and urinary chromium (CrR, CrU), and chromium in whole blood and in erythrocytes (CrBl, CrEry) in welders. Methods: Respirable welding fume was collected in 241 welders during a working shift. Blood samples and spot urine samples were collected after the working shift. The content of CrR in the welding fume was determined using inductively coupled plasma mass spectrometry. CrU, CrBl and CrEry were measured by means of graphite furnace atom absorption spectrometry. Linear regression models were applied to model exposure to chromium. A multiple imputation approach was chosen to account for values below the limit of quantitation (LOQ). Results: Median concentrations of CrR were <3.80 µg/m³, with about 23% below LOQ. Major determinants of the CrR were the chromium content in the electrodes or base material in addition to the type of welding. Airborne exposure was higher when welding was performed under inefficient ventilation. CrR correlated strongly with CrU (Pearson's correlation r = 0.61). Median concentrations of CrU were <1.20 µg/m³, and 44% of CrU measurements were below LOQ. CrU exposure decreased by a factor of 0.66 when a respiratory mask was used. Most measurements of CrBl and CrEry were below LOQ. All 15 welders with a measurable concentration of CrEry had high chromium contents in the materials (above 5%). Conclusions: CrR was mainly influenced by the chromium content in the materials and the welding process. Welding in confined space increased exposure to CrR. Efficient local exhaust ventilation and the use of respirators decreased exposure. Airborne Cr concentration was a good predictor of urinary Cr exposure.